Revision of the Hycleus sexmaculatus species group (Coleoptera: Meloidae, Mylabrini) - Serri, Sayeh; Bologna, Marco A.; Riccieri, Alessandra (Zootaxa, 2020)
In this study, the blister beetles belonging to the Hycleus sexmaculatus species group are revised. Morphological characters are described and figured for each species and keys to both male and female are provided. Hycleus hayki new species from Southwest Iran is described and the following new synonymies are proposed: Mylabris triangulifera ab. reitterioides Mader 1929 = Hycleus bipunctatus (Olivier, 1811) new synonymy; Mylabris triangulifera ab. bushirensis Mader 1929 = Hycleus bipunctatus (Olivier, 1811) new synonymy; Mylabris javeti Marseul, 1870 = Hycleus colligatus (Redtenbacher, 1850) new synonymy; Mylabris javeti umbilicatus Kaszab, 1958 = Hycleus colligatus (Redtenbacher, 1850) new synonymy; Hycleus amrishi Makhan, 2012 = Hycleus cingulatus (Faldermann, 1837) new synonymy. Additional remarks which rectify previous errors in the identification of the species are provided. The taxonomic positions of Zonabris soumacovi Pic, 1930 and Zonabris sialanus Pic, 1929 are also discussed. Phylogenetic relationships of the species, based on a subset of available species inferred from molecular data are proposed, and some morphologically defined subgroups of species are distinguished with the molecular support. The geographic and ecological distributions of all the species are defined, and a detailed list of localities is provided. The ecological information including phenology, elevation and host plants of the species are summarized in a table. Based on literature records, collections and recently collected data, the distribution of the sexmaculatus species and their biogeographic characteristics are discussed.